MONTE CARLO SIMULATIONS OF RADON-SEISMO-IONOSPHERIC TRILOGY IN SOME PARTS ON THE NORTH ANATOLIAN FAULT ZONE - MUHAMMAD, AHMAD (Fırat Üniveristesi, 2022)
For decades, researchers have examined the relationship between seismicity and Ionospheric variability (Karpov et al., 2012; Nesterov et al., 2019; Pulinets et al., 2015; Sorokin et al., 2001). The increase in radon exhalation rate during or near seismic activities, was one of the reasons why scientist claim its relationship with seismicity (Barkat et al., 2018; Fu et al., 2017; Ghosh et al., 2007; Külahcı and Şen, 2014; Pulinets et al., 1999; Segovia et al., 2005; Singh et al., 2017). Radon decays by ionizing the surroundings when it reaches the soil surface. Moreover, its progeny polonium and bismuth decay by ionizing the atmosphere and also enhancing aerosol charges when attached. The half-life of 222Rn as well as its ubiquity made it the best candidate ionization source in the lower atmosphere besides cosmic radiation. In this research, we will conduct a comprehensive study on radon time series near some of the most seismically active places in Turkey (alone major fault lines). Besides studying how it relates to earthquake, we shall also analyze the ionospheric anomalies related to this events.

For decades, researchers have examined the relationship between seismicity and Ionospheric variability (Karpov et al., 2012; Nesterov et al., 2019; Pulinets et al., 2015; Sorokin et al., 2001). The increase in radon exhalation rate during or near seismic activities, was one of the reasons why scientist claim its relationship with seismicity (Barkat et al., 2018; Fu et al., 2017; Ghosh et al., 2007; Külahcı and Şen, 2014; Pulinets et al., 1999; Segovia et al., 2005; Singh et al., 2017). Radon decays by ionizing the surroundings when it reaches the soil surface. Moreover, its progeny polonium and bismuth decay by ionizing the atmosphere and also enhancing aerosol charges when attached. The half-life of 222Rn as well as its ubiquity made it the best candidate ionization source in the lower atmosphere besides cosmic radiation. In this research, we will conduct a comprehensive study on radon time series near some of the most seismically active places in Turkey (alone major fault lines). Besides studying how it relates to earthquake, we shall also analyze the ionospheric anomalies related to this events.
Monte Carlo simulations of radon-seismo-ionospheric trilogy in some parts on the North Anatolian fault zone
Keywords: Bilim ve Teknoloji